A Bibliometric Approach to the Thesis of the Happy-Productive Worker—A Journey Through the Concepts and Measurement - Natália Costa; Pedro Ferreira; Carlos Miguel Oliveira (SAGE Open, 2024)
In an organizational context marked by a concern for well-being, decent working conditions, and the proliferation of events associated with happiness, a theory called the happy-productive worker thesis (HPW) emerged. This thesis is based on the premise that happy workers are more productive than their opposites. Therefore, managing organizations focusing on the internal customers (employees) seems a win-win situation for both parties. In this sense, this study aims to analyze the extent to which the HPW thesis has been explored theoretically and empirically, as well as the forms of measurement used to evaluate happiness and performance. This study presents a systematic literature review that defines the “happiness productive worker” as the key term to search on the Web of Science and Scopus databases. This study analyzes seven literature reviews and 38 articles. With these articles, the investigators used the VOSviewer to develop a keyword co-occurrence analysis. This methodology analyzes the strength between keywords, establishing an association between them. The results made it possible to divide the articles analyzed into three clusters: HPW and positive psychology, HPW and happiness measurement, and HPW and the association between the measurement of happiness and performance. This work concluded that of the 38 articles and seven reviews analyzed, all approved empirically and theoretically the premise that happy employees are more productive than their opposites and listed the main scales used.